Systems Thinking Pedagogical Design: Developing a Veteran-Centric Masters Degree In Cybersecurity and Leadership (Journal of The Colloquium for Information Systems Security Education, 2015)
Cybersecurity is a promising area because business, military, government, and utilities all desire trained cybersecurity professionals that can lead and effect change. Post-9/11 veterans represent a large untapped pool of talent ideal for addressing the nation's shortage of senior cyber leaders. But veterans often have difficulty transitioning to the civilian workforce. If they are to take advantage of the opportunity to usher military veterans into careers as cybersecurity leaders, universities need to engage in systems thinking pedagogical design. This paper introduces and assesses the utility of one approach for design as suggested by the KBP Pedagogical Model (Endicott-Popovsky & Popovsky, 2014). We use UW Tacoma's experience in mounting a new Master's level degree program in Cybersecurity and Leadership (the MCL) as a test case to evaluate the utility of this model for developing a veteran-centric approach to cyber security education. A retrospective analysis reveals the model to provide a useful frame for how to design the content of the curriculum and how it should be taught, but that it should be extended to address additional elements at the organizational level. Mechanisms to ensure strong and ongoing structural linkages between university schools support the interdisciplinary nature of the curriculum, control systems in the form of ongoing curricular evaluations methods support ongoing learning and the deep incorporation of non-faculty recruiting and advising capabilities into the administrative organization supports the students and ongoing ability of the faculty to adjust and deliver the curriculum. Each of these organizational design elements are critical features that enhance the performance of the pedagogical system and lower the risk of developing a new degree program that serves the needs of the transitioning veteran.